The Reality of Crisis Management in Jordanian Public Universities from the Perspective of Academic Leaders - Hiba Hussein Al-Momani (دراسات: العلوم التربوية, 2022)
Objective: This study aims to identify the reality of crisis management in Jordanian public universities during the Covid-19 pandemic from the perspective of academic leaders in those universities.